Marketing accountability for marketing and non-marketing outcomes - Kumar, V.,; Stewart, David W.,; Malhotra, Naresh K., (Review of marketing research ;, 2021)
This latest volume of Review of Marketing Research, Marketing Accountability for Marketing and Non-Marketing Outcomes is divided in three parts: (1) measures of firm performance, (2) measures of social interaction, and (3) measures related to broader societal outcomes such as sustainability and quality of life. Measures of firm performance covered include the marketing implications of financial accounting, customer feedback metrics, drivers of brand equity, brand failure, market orientation capabilities, and multichannel attributions. Measures of social interaction encompass environmental and social performance, social networks, and attitudinal word-of-mouth drivers. The final -- Chapter is devoted to measures related to societal outcomes and focuses on attractiveness of inner city for society. Each -- Chapter presents thought-provoking discussions and new insights which will be relevant to researchers, professionals and students of marketing, branding and consumer behaviour.